Sistem Informasi Data Penghasilan Driver Di Projek Official Menggunakan SMS Gateway - aji saputra; zaenanal Hakim; Lili Sujai; Robby Rizky (SITUSTIKA FIKUNMA, 2024)
PROJEK Official is a company engaged in the field of online transportation facilities in Pandeglang City, Banten, apart from being a means of transportation. delivery of information about driver income which is still submitted manually by coming to the office and asking for information about income and not compatible with confirmation SMS, therefore the results of the analysis that I get will create an information system by having a solution to build "Project Driver Income Data Information System Official Using Sms Gateway”. The system will be built on a website-based basis using the PHP, Java & Bootstrap programming languages and designed using a structured design starting from making Flow Of Systems (FOS), Contex Diagrams, DFD Levels, Entity Relationship Diagrams (ERD), Normalization, Data Dictionary, Database Structures, and the design of the output process input that results in the delivery of driver income by way of confirmation via SMS Gateway, and to make it easier for project drivers to find out income data information and implement the results of an official project driver income data information information system application that uses an SMS gateway. This system can help admins or PROJECT drivers in determining and finding information about income data that drivers get